BATASAN YUDISIALISASI POLITIK OLEH MAHKAMAH KONSTITUSI: PARADOKS UNDANG-UNDANG PEMILIHAN UMUM - Kishan, Marcelino Ceasar (Universitas Kristen Satya Wacana, 2024)
Abstract This paper aims to discuss the position of the Constitutional Court of the Republic of Indonesia in political judicialization. Judicialization of politics has become a critical issue because there is an intense debate on the choice of judicial restraint or judicial activism, particularly concerning its implications for the general election process. On this issue, this paper provides an alternative view related to the position of judicial restraint or judicial activism in a contextual manner, which departs from the limitation of the formation of General Election regulations that political judicialization must fill the legal vacuum caused by the finality of the General Election law which depends on delegated regulations. In adjudicating, the Constitutional Court of the Republic of Indonesia must perform policy calculations to determine how to correct the norms of the annulled General Election law.